Determination of high molecular mass compounds from Amazonian plant's leaves - Siqueira, Denilson Soares de; dos Santos Pereira, A. S.; Aquino Neto, Francisco Radler; Cabral, José Augusto; Ferreira, Carlos Alberto Cid; Simoneit, Bernd Rolf Tatsuo; Elias, Vladimir O. (Química Nova, 2003)
The fractIons of dichloromethane extracts of leaves from andiroba (Carapa guianensis - Meliaceae), caapi (Banisteriopsis caapi - Malpighiaceae), cocoa (Theobroma cacao - Sterculiaceae), Brazil nut (Bertholletia excelsa - Lecytidaceae), cupuaçu (Theobroma grandiflorum - Sterculiaceae), marupá (Simaruba amara - Simaroubaceae) and rubber tree (Hevea brasiliensis - Euphorbiaceae), were analyzed by HT-HRGC and HT-HRGC-MS. Esters of homologous series of fatty acids and long chain alcohols, phytol, amyrines and tocopherols were characterized. The characterization of the compounds was based mainly in mass spectra data and in addition by usual spectrometric data (1H and 13C NMR, IR).
Determinação de compostos de massa molecular alta em folhas de plantas da Amazônia
Keywords: Banisteriopsis Caapi Extract; Bertholletia Excelsa Extract; Carapa Guianensis Extract; Hevea Brasiliensis Extract; Plant Extract; Simaruba Amara Extract; Theobroma Cacao Extract; Theobroma Grandiflorum Extract; Unclassified Drug; Banisteriopsis Caapi; Brazil Nut; Cacao; Carapa Guianensis; Carbon Nuclear Magnetic Resonance; Chemical Analysis; Chemical Structure; Controlled Study; Data Analysis; Euphorbia; Extraction; Gas Chromatography; Hevea Brasiliensis; Malpighiaceae; Mass Spectrometry; Meliaceae; Molecular Weight; Nonhuman; Plant; Plant Leaf; Proton Nuclear Magnetic Resonance; Simaroubaceae; Simaruba Amara; Sterculiaceae; Structure Analysis; Theobroma Grandiflorum